A cross-cultural comparison of dietary intakes and physical activity between American and Czech school-aged children - Humenikova Shriver, Lenka; Gates, Gail (Public health nutrition, 2009)
OBJECTIVE: The prevalence of child overweight in the Czech Republic is substantially lower than that in the USA. The objective of the present pilot study was to explore dietary intakes, frequency of dining in fast-food establishments, and the amount and intensity of physical activity between a sample of American and Czech children. DESIGN: A cross-sectional correlational pilot study. SETTING: Four public schools in the USA and four public schools in the Czech Republic. SUBJECTS: Ninety-five Czech and forty-four American 4-6th graders from urban public schools participated in the study. Dietary intake and number of fast-food visits were evaluated using two multiple-pass 24 h recalls. Physical activity was measured using the modified Self-Administered Physical Activity Checklist. RESULTS: American children (mean age 10.8 (SE 0.2) years) consumed more energy and fat, less fruits and vegetables, more soft drinks, and visited fast-food establishments more often than Czech children (mean age 11.0 (SE 0.1) years). Although no differences were found in vigorous activity by nationality, Czech children spent significantly more time in moderate physical activities than American children. CONCLUSIONS: Despite the influx of some negative Western dietary trends into the country, Czech children had a healthier diet and were more physically active than American children. Further research is warranted to determine whether the same differences in dietary intakes, physical activity and fast-food visits exist between nationally representative samples of American and Czech children.
Keywords: Female; Overweight; Prevalence; Vegetables; dítě; energetický příjem; srovnání kultur; rozpomínání; ženské pohlaví; průřezové studie; dietní tuky; zelenina; lidé; cvičení; Energy Intake; Mental Recall; Pilot Projects; Child Nutritional Physiological Phenomena; pilotní projekty; Carbonated Beverages; Fruit; sycené nápoje; dieta; ovoce; prevalence; Spojené státy americké; Cross-Sectional Studies; Diet; Male; Czech Republic; Cross-Cultural Comparison; nadváha; index tělesné hmotnosti; United States; Česká republika; Child; mužské pohlaví; fyziologie výživy dětí; Body Mass Index; Exercise; Dietary Fats; Humans